2019
DOI: 10.3390/nu11081887
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Endotoxemia: A Potential Underlying Mechanism of the Relationship between Dietary Fat Intake and Risk for Cognitive Impairments in Humans?

Abstract: (1) Background: Nutrition is a major lifestyle factor that can prevent the risk of cognitive impairment and dementia. Diet-induced metabolic endotoxemia has been proposed as a major root cause of inflammation and these pathways emerge as detrimental factors of healthy ageing. The aim of this paper was to update research focusing on the relationship between a fat-rich diet and endotoxemia, and to discuss the potential role of endotoxemia in cognitive performances. (2) Methods: We conducted a non-systematic lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 82 publications
2
40
0
Order By: Relevance
“…In particular, previous studies have demonstrated that a healthy microbiota limits excessive inflammation and alleviates inflammatory disorder pathology by inducing Tregs via the excretion of short chain fatty acids (SCFAs) and immunomodulatory AHR ligands ( Vinolo et al, 2011 ; Rothhammer and Quintana, 2016 ). However, the potential of the microbiome in inflammatory disorders serves as a double-edged sword due to chronic intestinal dysbiosis being demonstrated to worsen and instigate inflammatory disorders ( Lee et al, 2011 ; Li et al, 2018 ; Opazo et al, 2018 ; Saltzman et al, 2018 ; André et al, 2019 ). These previous studies have established that disparity in the microbial composition along barrier sites is directly involved with the clinical outcome of inflammatory disorders afflicting the host organism, and therefore suggest further studies focused on the etiological role of the microbiome in inflammatory diseases in order to develop novel therapeutics and identify biomarkers for early detection.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous studies have demonstrated that a healthy microbiota limits excessive inflammation and alleviates inflammatory disorder pathology by inducing Tregs via the excretion of short chain fatty acids (SCFAs) and immunomodulatory AHR ligands ( Vinolo et al, 2011 ; Rothhammer and Quintana, 2016 ). However, the potential of the microbiome in inflammatory disorders serves as a double-edged sword due to chronic intestinal dysbiosis being demonstrated to worsen and instigate inflammatory disorders ( Lee et al, 2011 ; Li et al, 2018 ; Opazo et al, 2018 ; Saltzman et al, 2018 ; André et al, 2019 ). These previous studies have established that disparity in the microbial composition along barrier sites is directly involved with the clinical outcome of inflammatory disorders afflicting the host organism, and therefore suggest further studies focused on the etiological role of the microbiome in inflammatory diseases in order to develop novel therapeutics and identify biomarkers for early detection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the high-fat diet from food caused the rise in circulating LPS. A state of chronic low-grade inflammation induced by systemic exposure to bacterial LPS is referred to as diet-induced metabolic endotoxemia 9 . Consistently, mice fed with a high-fat diet for 4 weeks showed an increase in plasma LPS by 2-or 3-fold, body fat, and expression of inflammatory cytokines and developed insulin resistance 10 .…”
mentioning
confidence: 99%
“…Suez et al ( 89 ) showed an altered host metabolism by downstream effects of microbiota in mice upon saccharin intake. The authors found enriched microbial pathways, associated with metabolic syndrome, in mice, including lipopolysaccharide (LPS) synthesis, which is a breakdown product of the outer membrane of Gram-negative bacteria ( 89 , 177 ). Microbiota dysbiosis is considered to be related to the loss of gut mucosal integrity as the expression of tight junction proteins is reduced, among other mechanisms ( 176 , 178 ).…”
Section: Glucose Homeostasismentioning
confidence: 99%
“…Microbiota dysbiosis is considered to be related to the loss of gut mucosal integrity as the expression of tight junction proteins is reduced, among other mechanisms ( 176 , 178 ). Therefore, LPS may translocate from the gut into the portal or systemic circulation, thereby able to stimulate the activation of pro-inflammatory macrophages and the secretion of pro-inflammatory cytokines ( 127 , 177 , 179 181 ). Other studies showed disrupted intestinal epithelial barrier in vitro using Caco-2 cells upon saccharin stimulation, whereas aspartame, acesulfame-K, and sucralose did not alter intestinal permeability ( 176 ).…”
Section: Glucose Homeostasismentioning
confidence: 99%